Asymmetric-flow field-flow fractionation for measuring particle size, drug loading and (in)stability of nanopharmaceuticals. The joint view of European Union Nanomedicine Characterization Laboratory and National Cancer Institute - Nanotechnology Characterization Laboratory - Prina Mello, Adriele (My University, 2021)
Asymmetric-flow field-flow fractionation (AF4) has been recognized as an invaluable tool for the characterisation of particle size, polydispersity, drug loading and stability of nanopharmaceuticals. However, the application of robust and high quality standard operating procedures (SOPs) is critical for accurate measurements, especially as these complex drug nanoformulations are most often inherently polydisperse. In this review we describe a unique international collaboration that lead to the development of a robust SOP for the measurement of physical-chemical properties of nanopharmaceuticals by multi-detector AF4 (MD-AF4) involving two state of the art infrastructures in the field of nanomedicine, the European Union Nanomedicine Characterization Laboratory (EUNCL) and the National Cancer Institute-Nanotechnology Characterisation Laboratory (NCI-NCL). We present examples of how MD-AF4 has been used for the analysis of key quality attributes, such as particle size, shape, drug loading and stability of complex nanomedicine formulations. The results highlight that MD-AF4 is a very versatile analytical technique to obtain critical information on a material particle size distribution, polydispersity and qualitative information on drug loading. The ability to conduct analysis in complex physiological matrices is an additional very important advantage of MD-AF4 over many other analytical techniques used in the field for stability studies. Overall, the joint NCI-NCL/EUNCL experience demonstrates the ability to implement a powerful and highly complex analytical technique such as MD-AF4 to the demanding quality standards set by the regulatory authorities for the pre-clinical safety characterization of nanomedicines.
Keywords: polydispersity; Asymmetric-flow field-flow fractionation (AF4); nanopharmaceuticals; Field flow fractionation; Regulatory framework; Standard operating procedures; Nanoparticle stability; Nanomedicine; Nanoparticle size distribution